Optimized Configuration of Diesel Engine-Fuel Cell-Battery Hybrid Power Systems in a Platform Supply Vessel to Reduce CO2 Emissions - Giovani T. T. Vieira; Derick Furquim Pereira; Seyed Iman Taheri; Khalid S. Khan; Mauricio B. C. Salles; Josep M. Guerrero; Bruno S. Carmo (Energies, 2022)
The main objective of this paper is to select the optimal configuration of a ship’s power system, considering the use of fuel cells and batteries, that would achieve the lowest CO2 emissions also taking into consideration the number of battery cycles. The ship analyzed in this work is a Platform Supply Vessel (PSV) used to support oil and gas offshore platforms transporting goods, equipment, and personnel. The proposed scheme considers the ship’s retrofitting. The ship’s original main generators are maintained, and the fuel cell and batteries are installed as complementary sources. Moreover, a sensitivity analysis is pursued on the ship’s demand curve. The simulations used to calculate the CO2 emissions for each of the new hybrid configurations were developed using HOMER software. The proposed solutions are auxiliary generators, three types of batteries, and a proton-exchange membrane fuel cell (PEMFC) with different sizes of hydrogen tanks. The PEMFC and batteries were sized as containerized solutions, and the sizing of the auxiliary engines was based on previous works. Each configuration consists of a combination of these solutions. The selection of the best configuration is one contribution of this paper. The new configurations are classified according to the reduction of CO2 emitted in comparison to the original system. For different demand levels, the results indicate that the configuration classification may vary. Another valuable contribution of this work is the sizing of the battery and hydrogen storage systems. They were installed in 20 ft containers, since the installation of batteries, fuel cells and hydrogen tanks in containers is widely used for ship retrofit. As a result, the most significant reduction of CO2 emissions is 10.69%. This is achieved when the configuration includes main generators, auxiliary generators, a 3,119 kW lithium nickel manganese cobalt (LNMC) battery, a 250 kW PEMFC, and 581 kg of stored hydrogen.